Chromosome bi-orientation in yeast - Stark, Mike; Tanaka, Tomo (Henry Stewart Talks, 2009)
Chromosome bi-orientation and aneuploidy, Modes of sister chromatid attachment to spindle microtubules, The budding yeast as a model for studying chromosome bi-orientation, Geometry-dependent mechanism of chromosome bi-orientation, Yeast Ipl1p kinase and chromosome bi-orientation, The yeast chromosomal passenger complex, Models for tension-sensing, The targets of Ipl1p kinase at the kinetochore, Update talk: Aurora B (Ipl1) kinase promotes error correction, Update talk: Aurora B and yeast kinetochore structure, Update talk: Aurora B localisation, Update talk: Spatial separation model, Update talk: Additional factors that promote error correction, Update talk: Microtubule dynamics and Stu2 affect error correction
Updated at 2022/01/30